Recent advances in passive cooling methods for photovoltaic performance enhancement - Ahmad, Emy Zairah; Sopian, Kamaruzzaman; Jarimi, Hasila; Fazlizan, Ahmad; Elbreki, Abdelnaser; Abd Hamid, Ag Sufiyan; Rostami, Shirin; Ibrahim, Adnan (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The electrical output performance of photovoltaic (PV) modules are sensitive to temperature variations and the intensity of solar irradiance under prolonged exposure. Only 20% of solar irradiance is converted into useful electricity, and the remaining are dissipated as heat which in turns increases the module operating temperature. The increase in module operating temperature has an adverse impact on the open-circuit voltage (Voc), which results in the power conversion efficiency reduction and irreversible cell degradation rate. Hence, proper cooling methods are essential to maintain the module operating temperature within the standard test conditions (STC). This paper presents an overview of passive cooling methods for its feasibility and economic viability in comparison with active cooling. Three different passive cooling approaches are considered, namely phase change material (PCM), fin heat sink, and radiative cooling covering the discussions on the achieved cooling efficiency. The understanding of the above-mentioned state-of-the-art cooling technologies is vital for further modifications of existing PV modules to improve the efficiency of electrical output.